Hubungan Antara Persepsi Siswa Terhadap Kinerja Guru Bimbingan dan Konseling dengan Kepercayaan Melakukan Konseling Individual - Weni Kurnia Rahmawati; Saidah Bibi (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2021)
The reason for this exploration is to decide if there is a connection between understudy impression of the exhibition of guiding instructors and the confidence in directing individual advising of class X understudies in MAN 1 Jember. This kind of exploration is quantitative examination. Information assortment techniques as meetings, documentation and surveys. Investigation of exploration information utilizing measurable estimations with SPSS. In view of the worth of r count (Pearson Correlations) it is realized that the worth of r count is 0.492> r table 0.184, it tends to be reasoned that there is a critical connection between's understudy impression of the presentation of directing educators with the variable of confidence in leading individual guiding. The worth of r count or Pearson Correlations shows a positive worth, which implies that the connection between the two factors is positive, or all in all the expanding understudy view of the presentation of guiding instructors will likewise build the trust in leading individual advising.